Особливості функціонування та виклики розвитку ЄС у близькій перспективі (2017–2018 рр.) - Дорош, Леся; Івасечко, Ольга; Dorosh, Lesya; Ivasechko, Olha (Lviv Politechnic Publishing House, 2017)
Розглянуто новітні внутрішні та зовнішні загрози ЄС у близькій перспективі (2017–2018 рр.), що зумовлені глобальними, регіональними та локальними тенденціями світового розвитку та зміною політичних, економічних та безпекових пріоритетів ЄС у контексті підписання Римської декларації 2017 р. До загроз та викликів ЄС на близьку перспективу зараховано: гібридні наслідки агресії Російської Федерації в Україні, міграційну кризу в Європі, серію терористичних актів у європейських містах, непередбачувану політику новообраного президента США Д. Трампа щодо європейської системи безпеки, посилення позиції крайніх лівих та правих політичних сил у європейських державах, “Брекзіт” та його наслідки, зокрема, загрозу “ефекту доміно” в інших державах-членах Співтовариства.

The authors consider the newest internal and external threats to the EU in the nearest future (2017-2018) which are determined by global, regional and local trends of world development and changes of political, economic and security priorities of the EU within the context of signing the Rome Declaration in 2017. It is asserted that the economic risks and strengthening of Euroscepticism are considered as traditional for the functioning of the EU. However, migration problems, the issues of hybrid impacts and other challenges which were not topical a few years ago should be added to the classic interpretations of threats facing functioning of the EU in the short and medium term. So, this is systematically considered as key challenges to the EU in 2017–2018, taking into account the interconditionality and interdependence of economic, security (hybridity of current conflicts and terrorism), institutional, social and other internal and external problems of the Community. Thus, one of the main internal problems of the EU is the institutional crisis (problem of “Brexit” and its consequences, in particular the threat of “domino effect” in otherMember States of the Community, creation of common future vision of the EU development, strengthening the position of the ultra leftwing and right-wing political forces in the European countries). Economic challenges, which are partially determined by external factors, are considered to be major problems as well. Key external threats are defined as follows: aggravation of security threats in the context of recent hybrid regional conflicts (Russian aggression in Ukraine), migration crisis, unpredictable policy on European security systemof the newly elected US President D. Trump, acts of terrorismin European cities as ameans of destabilization of the internal situation in the EUmember states. The authors analyse the Rome Declaration 2017 implementing of which can become the strategic foundation for formation of an adequate response to urgent internal and external challenges of the EU development.
Peculiarities of functioning and challenges of the EU development in the short term perspective (2017–2018)
Keywords: новітні загрози ЄС; міграція; тероризм; Римська декларація 2017 р.; “Брекзіт”; агресія; the newest threats to the EU; migration; terrorism; the Rome Declaration 2017; “Brexit”; aggression; 327.7; 327.82; 341.1